Kat, ofiara i świadek w "Śmierci i dziewczynie" Romana Polańskiego - Aleksandra Piętka (Załącznik Kulturoznawczy)
This paper analyzes the cinematographic means used by Roman Polanski in Death and the Maiden to portray the characters of the movie and the relationship between them. It discusses how Polanski toys with the thriller convention to create a cognitive dissonance in the viewer and uses artistic devices to reflect the process of restoring the identity by the protagonist. In particular, the author examines the frame of the movie and its compositional and semantic functions and compares selected scenes with René Magritte’s paintings to show how the director depicts the experience of the main character and the blurring of boundaries between the perpetrator and the victim. Also, colors, props, and landscape motifs associated with each character are analyzed to explain their symbolic and dramatic function in the film.